Effects of Group IB Metals of Au/Ag/Cu on Boosting Oxygen Evolution Reaction of Cobalt Hydroxide. Issue 7 (17th March 2023) - Wang, Xianchao; Zang, Zehao; Fan, Chunyan; Zhang, Yintao; Li, Xiang; Li, Lanlan; Yu, Xiaofei; Yang, Xiaojing; Lu, Zunming; Zhang, Xinghua
Abstract: Developing high‐activity, good‐stability oxygen evolution reaction (OER) catalysts is the key to solving the problem of hydrogen production from electrolytic water. Cobalt hydroxide (Co(OH)2 ) is a hopeful OER catalyst, but its poor conductivity and low inherent activity limit its OER performance. Herein, we used group IB metals of Au, Ag, and Cu to increase the OER performance of Co(OH)2 via the electrodeposition method. All three metals can increase the carrier concentration and proportion of high‐valence cobalt ions. The analysis results disclose that the construction of Ag−Co(OH)2 heterostructure can optimize the electronic structure through interfacial interactions, produce a moderate proportion of high‐valence cobalt centers, enhance the charge transport capacity and the adsorption of hydroxyl species, thus accelerating the OER kinetics and effectively improving the inherent catalytic activity. This work not only develops effective and steady catalysts but also provides a facile method to enhance the OER performance through interface engineering. Abstract : High OER performances : The M−Co(OH)2 composite electrocatalyst was prepared by electrodeposition to improve the oxygen evolution reaction (OER) performance. The effects of IB group metal elements on the OER performance and electronic structure of Co(OH)2 were investigated.